Late Republican and Early Empire common ware in Southern Lusitania (Algarve-Portugal): the Italian Imports - Viegas, Catarina (Rei Cretariae Romanae Fautorum Acta, 2022)
Recent research on common wares from different Algarve sites has provided relevant information concerning different types of imported material, as well as on local and regional productions. This paper presents the data concerning Italian common ware that was distributed in southern Lusitania (today Algarve-Portugal) in the Roman Republic and Early Empire. The main forms identified are the unslipped common ware from Campania: platters and lids and Pompeian-Red ware platters. Common ware from the Roman towns of Balsa (today Torre de Ares, Tavira), Baesuri (Castro Marim) and Ossonoba (Faro) and elsewhere show that most of the vessels have their origin in Ulterior/Baetica. Apart from Roman towns in eastern and central Algarve, sites such as Loulé Velho (which could have been a Roman villa or even a vicus) provided examples of Pompeian-Red ware, showing that the distribution of these vessels spread beyond the strict urban sphere, as also Dramont D2 mortaria from Central Italy testify. The Algarve towns such as Balsa (Torre de Ares Tavira) were particularly open to Mediterranean trade. The identification, for the first time in southern Lusitania, of a few examples of a Syracusan ‘ceramica comune tipo San Giuliano’ was confirmed.